The Role of Beauty Pageants in Developing English Speaking Skills and Self-Confidence Among Beauty Pageant Participants - Nabila Tanisa; Yeni Rahmawati; Dzul Rachman (FKIP, Universitas Palangka Raya, 2026)
The ability to communicate effectively in English and to demonstrate strong self-confidence is essential for beauty pageant participants, particularly in activities involving public interaction. Beauty pageants have evolved beyond competitions focused solely on physical appearance by emphasizing communication skills, leadership, public speaking, and social advocacy. These characteristics position beauty pageants as meaningful environments for developing English-speaking competence and self-confidence. This study investigates the contribution of beauty pageants to the development of English-speaking skills and self-confidence among beauty pageant participants. An explanatory sequential mixed-methods design was employed. Quantitative data were collected via questionnaires administered to 100 participants who had participated in beauty pageants or pageant auditions between 2022 and 2026. Qualitative data were subsequently obtained through semi-structured interviews with six participants representing high, medium, and low questionnaire score categories. Descriptive statistics were used to analyze the quantitative data, while thematic analysis was used to analyze the qualitative data. The findings indicate that beauty pageants contribute positively to the development of English speaking skills by providing authentic opportunities for public speaking, interviews, advocacy presentations, and interpersonal communication. The study also reveals that repeated participation, continuous practice, and constructive feedback help participants develop greater self-confidence when communicating in English. These findings highlight the potential of beauty pageants as experiential learning environments that support both communication competence and personal development.